2012
DOI: 10.5194/isprsarchives-xxxix-b4-171-2012
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the New Worldview-2 Spectral Bands for Urban Mapping in Coastal Areas: Case Study São Luís ( Maranhão State, Brazil)

Abstract: ABSTRACT:The objective of this study is to verify the contribution of the spectral bands from the new WorldView-2 satellite for the extraction of urban targets aiming a detailed mapping from the city of São Luis, at the coastal zone of Maranhão State, Brazil. This satellite system has 3 bands in the visible portion of the spectrum and also the following 4 new bands: Coastal (400-450 nm), Yellow (585-625 nm), Red Edge (705-745 nm), and Near Infrared 2 (860-1040 nm). As for the methodology used, initially a fusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…The yellow band was found to be effective in the identification of bare soils (see Figure 4), which concurs with the findings of Souza & Kux (2012). The inclusion of image texture (Haralick et al 1973;Blaschke et al 2014) can assist with the classification process and has been found to increase classification accuracies (Aguilar et al, 2013;Franklin and Peddle, 1990).…”
Section: Image Classificationsupporting
confidence: 77%
“…The yellow band was found to be effective in the identification of bare soils (see Figure 4), which concurs with the findings of Souza & Kux (2012). The inclusion of image texture (Haralick et al 1973;Blaschke et al 2014) can assist with the classification process and has been found to increase classification accuracies (Aguilar et al, 2013;Franklin and Peddle, 1990).…”
Section: Image Classificationsupporting
confidence: 77%